ISLAMIC ACEHNESE IDENTITY, SHARIA, AND CHRISTIANIZATION RUMOR: A Study of the Narratives of the Attack on the Bethel Church in Penauyong Banda Aceh (JOURNAL OF INDONESIAN ISLAM, 2016)
This paper explores the narratives of the attack on the Bethel church (GBI/Gereja Bethel Indonesia) in Penauyong Aceh on June 17, 2012, provided for by the victims. Among these are those who hold fear of Christian missionaries, including one of the likely perpetrators, and those who dismissed these as mere rumors. After relating the incident to other violence across the nation during the reform period and to the local Aceh context, the paper delved into the interviews undertaken on July 2013, from which the sources of narratives were taken, explaining motivations behind the mob, trauma resulting from it, and other factors contributing to the incident. Through this article I argue that the sharia implementation  raise the new identity formulation of Islamic Acehnese, through which the dividing line between ‘Muslims’ and others ‘non-Muslims’ is further stressed. This in turn nurtures, among other things, the sentiments among the Acehnese against the non-Muslims.